Regulatory Systems in Bone Marrow for Hematopoietic Stem/Progenitor Cells Mobilization and Homing. (17th June 2013) - Alvarez, P.; Carrillo, E.; Vélez, C.; Hita-Contreras, F.; Martínez-Amat, A.; Rodríguez-Serrano, F.; Boulaiz, H.; Ortiz, R.; Melguizo, C.; Prados, J.; Aránega, A.
Abstract : Regulation of hematopoietic stem cell release, migration, and homing from the bone marrow (BM) and of the mobilization pathway involves a complex interaction among adhesion molecules, cytokines, proteolytic enzymes, stromal cells, and hematopoietic cells. The identification of new mechanisms that regulate the trafficking of hematopoietic stem/progenitor cells (HSPCs) cells has important implications, not only for hematopoietic transplantation but also for cell therapies in regenerative medicine for patients with acute myocardial infarction, spinal cord injury, and stroke, among others. This paper reviews the regulation mechanisms underlying the homing and mobilization of BM hematopoietic stem/progenitor cells, investigating the following issues: (a) the role of different factors, such as stromal cell derived factor-1 (SDF-1), granulocyte colony-stimulating factor (G-CSF), and vascular cell adhesion molecule-1 (VCAM-1), among other ligands; (b) the stem cell count in peripheral blood and BM and influential factors; (c) the therapeutic utilization of this phenomenon in lesions in different tissues, examining the agents involved in HSPCs mobilization, such as the different forms of G-CSF, plerixafor, and natalizumab; and (d) the effects of this mobilization on BM-derived stem/progenitor cells in clinical trials of patients with different diseases.